The Influence of Mathematical Logical Intelligence on Problem Solving Ability in Solving Story Problems - Puji Astuti; M. Saidun Anwar; Choirudin Choirudin; Anindya Eka Juarlan; Emmanuel Hagenimana (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
Students typically need help understanding a succession of stories, relating mathematical concepts, and formulating them logically, systematically, and critically. Thus, students' math skills still need to improve. Students' mathematical intelligence, which has yet to be employed to solve story-form questions, affects their math abilities. This study examines MTs Walisongo Sukajadi class VIII students' mathematical and logical abilities. This research is quantitative and ex post facto. This study included 25 MTs Walisongo Sukajadi class VIII pupils. This study randomly selected 25 pupils from the population. Data is collected using surveys and tests. Data analysis uses Simple Linear Regression. This research found that Y = -8.728 + 0.958X is the regression equation from the analysis above. Statistical hypothesis testing yields Fcount = 50.200 and Ftable = 4.22. Since Fcount > Ftable and 0.000 > 0.05, H0 was rejected. This suggests that mathematical and logical intelligence positively and significantly affects SPLDV tale problem-solving. The R2 value of 0.686 shows how much mathematical and logical intelligence affects problem-solving. After utilizing the determinant method was 68.6%, meaning logical intellect contributed 68.6% to problem-solving, whereas other variables contributed 31.4%.